Os conflitos escolares nos anos finais do Ensino Fundamental - Pinheiro, Osana Barbosa de Abreu (2016)
This research aims to identify, analyze and understand, regarding the students’ point of view, teachers and managers. What are the school’s conflicts and why they occur involving young students at the end of elementary school II. Focused on the conflicts which often occur inside a ninth grade classroom from elementary II at a municipal public school in the metropolitan region of Sao Paulo. Based on experiences which were lived in the school daily life, it is possible to attest that most students on the age bracket of 12 to 14 years, show a noticeable change on their behavior when they join elementary school II. They manner how they act and react in the school daily life is quite different from when they joined their first years at school. When they get to the conclusion years of cycle II (research focus), the problem is remarkable and the issues faced for educators get considerably highlighted. These behavior and mindset changes have left managers, teachers and parents concerned, due to that, the school gets in charge of such a huge challenge to be faced. When asked, students defend themselves, showing their reasons, and the same behavior occurs with adults. These are questions that go around the research: Why students from the end of Elementary school, especially those from 9th grade, lose their interest about the knowledge they can acquire, and begin to create the conflicts inside school? What are these student’s, teacher’s and manager’s goals on finding a solution to this problem? The research was done focusing on Portuguese Language, which has shown low learning indexes on external evaluations. The theoretical contributions were from the following authors: Xésus R. Jares – due to his studies about school as a place of conflicts; François Dubet, Danilo Martucelli Bernard Charlot, who analyze the school as a place of inequalities and the relation between students and knowledge; Emílio Tenti Fanfani and Gimeno Sacristán who discuss the schools’ council, its curriculum, its culture, the students’ culture and the teacher’s function on building a curriculum turned to the student. It’s a qualitative research, carried to the use of documentary analyses and interviews. The occurrence records were analyzed, as well as others materials, such as: Pedagogical Political Project, Projects against shifts, management rules and coexistence, process of continuing education to teachers, specifics federal and municipal laws. Beyond that, interviews were performed in a group of 06 students, 02 teachers and 01 school manager. The results obtained were presented on frames of summary information and revealed that there are conditions inside school reality, which allow and make the conflicts even easier to occur, especially those regarding students who are in the school phase and lives that tend to conflicts. The types of conflicts found on the school’s record and those which are noticed and expressed by teachers, manager and students, were focused on the behavior of resistance and disinterest shown by students, revealed the importance of school’s actions to reverse such situation